For Derrida - Miller, J. Hillis (Joseph Hillis), 1928-2021 (Fordham University Press, 2009)
This book, written by an author who was a close friend of Jacques Derrida for 40 years, is 'For Derrida'in two ways. Firstly, it is dedicated to his memory. Secondly, it acts as an advocate for his work. the chapters focusing especially on his late work, including passages from the last, as yet unpublished seminars.